PERBANDINGAN PENDAPATAN USAHA TANI PADI SAWAH ANTARA METODE TANAM PINDAH (TAPIN) DAN TANAM BENIH LANGSUNG (TABELA) DI DESA MEKARUO KECAMATAN DUMOGA BARAT KABUPATEN BOLAANG MONGONDOW - Rian Jetsi Wosal; Nordy Fritsgerald Lucky Waney; Audrey Julia Maria Maweikere (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine how much difference the income of lowland rice farming with the Moving Planting Method (Tapin) and Direct Seed Planting (Tabela) in Mekaruo Village, Dumoga Barat District, Bolaang Mongondow Regency. The research was conducted from March to May 2019. The data sources in this study used primary and secondary data. Primary data is through direct interviews with respondent farmers using a questionnaire. Secondary data is data obtained through the agencies involved in this study. Respondents in this study were lowland rice farmers in the village of Mekaruo. The data analysis used in this research is quantitative descriptive analysis through the calculation of gross income, total costs, and fixed costs incurred during one growing season. The results showed that the income of lowland rice farming with direct seed planting method was greater than the income of transplanted lowland rice. Comparison of farm income that applies the transplanting method (Tapin) with the average value. Rp. 7,851,083 and farmers who applied the direct seed planting method (Tablea) with an average value. Rp. 11,083,767 in Mekaruo Village, seen from the comparison of the average farm income cultivated.*eprm*